2018
DOI: 10.29271/jcpsp.2018.05.381
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Chewable Tobacco

Abstract: In Pakistan, extensive use of several precarious chewable tobacco formulations has made oral cancer the second leading malignancy. Selection of literature was done by a survey of studies published from 1990 to 2017 mainly, from PUBMED and few from other search engines, on naswar, gutka, areca nut and betel quid, which included published reviews, original articles and other data sources on chewable tobacco, its epidemiology, pathological implications, and psychological effects. These studies have revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…17 These are kept in mouth for several hours, thus exposing the mucosa to the chemicals and thus increased chances of developing oral submucosal fibrosis and oral cancers. 18 Importantly, knowledge regarding the detrimental effects of smokeless tobacco is poor in Karachi. 19 Therefore, relevant intervention by concerned authorities can play a vital role in controlling this preventable cancer.…”
Section: Discussionmentioning
confidence: 99%
“…17 These are kept in mouth for several hours, thus exposing the mucosa to the chemicals and thus increased chances of developing oral submucosal fibrosis and oral cancers. 18 Importantly, knowledge regarding the detrimental effects of smokeless tobacco is poor in Karachi. 19 Therefore, relevant intervention by concerned authorities can play a vital role in controlling this preventable cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depending on the cultivated soils and production processes, some unusually high levels of known components and unexpected toxins have been identified in SLT leaves [9,10]. Recent international studies revealed serious health concerns related to SLT consumption, specifically oral health impairment [11,12], nutritional disorders [13], co-use of psychoactive substances, and cardiovascular disease [14][15][16]. In Burkina Faso, no previous study using a representative sample has reported the national prevalence of SLT use and its health-related consequences in rural areas, particularly among females.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine causes dependence and a higher nicotine level coupled with a high pH can cause stronger cravings and more frequent and/or prolonged use of the SLT products [ 35 ], leading to a stronger exposure to the carcinogenic agents. There are also suggestions that Naswar causes local tissue trauma by erosion [ 36 ], and chronic tissue trauma is an independent risk factor for cancer [ 37 ]. The ash and lime used in the preparation of Naswar may also be contributing a high level of toxins and heavy metals to the composition, thus adding to its potential toxicity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%